Resilience Analysis of Lake Lot Tawar Coastal Communities to Changes in the Maritime Environment: A Case Study in Aceh Tengah - Sabaruddin, Sabaruddin; Muhammad David; Romadhoni, Dita; Anwar, Thaibil; Baihaqi; Putu Suarsana (Meteor STIP Marunda, 2024)
Changes in the maritime environment, such as ecosystem degradation, climate change and human activities, pose major challenges to coastal communities. This research aims to analyze the level of resilience of coastal communities of Lake Lot Tawar in Central Aceh District to changes in the maritime environment. The approach used in this research is a qualitative method with a case study, where primary data is obtained through in-depth interviews with local stakeholders, as well as field observations. The results show that the level of resilience of coastal communities in this region is influenced by various factors, including socio-economic conditions, government policies, and the level of public awareness of the importance of environmental conservation. Communities that have active involvement in sustainable economic activities, as well as access to information and support from government and non-government institutions, tend to be more resistant to the impacts of environmental change. The study also found a need to improve the adaptive capacity of communities through environmental education programs and adaptation skills training. In conclusion, the resilience of Lake Lot Tawar coastal communities to changes in the maritime environment can be improved through a holistic approach involving various stakeholders.